Diagnostic Value of Muscle [11C] PIB-PET in Inclusion Body Myositis - Noto, Yu-ichi; Kondo, Masaki; Tsuji, Yukiko; Matsushima, Shigenori; Mizuno, Toshiki; Tokuda, Takahiko; Nakagawa, Masanori (Frontiers in Neurology, 2020)
Background: The accumulation of multiple-protein aggregates within muscle fibers is a pathological hallmark of sporadic inclusion body myositis (s-IBM) with the presence of inclusion bodies. Amyloid-beta is one of the accumulated proteins in s-IBM. The aim of this study was to elucidate the utility of Pittsburgh compound B-positron emission tomography (PIB-PET) for diagnosing s-IBM. Methods: Nine patients with s-IBM and 4 patients with idiopathic inflammatory myopathy (IIM) were included. Patients underwent PIB-PET of body muscles. Standardized uptake values (SUVs) were measured in 16 muscles. A comparison of SUVs was made between s-IBM and IIM groups. The correlation between PIB-PET and clinical parameters was analyzed. Results: The mean SUV of all muscles in s-IBM patients was higher than in IIM patients (0.32 vs. 0.25, respectively; p = 0.031). Subgroup analysis identified a clear difference in SUVs of the forearm and lower-leg muscle groups (p = 0.021 and p = 0.045, respectively). There was no correlation between SUVs and clinical parameters in s-IBM patients. Conclusions: Muscle PIB-PET may help to make a diagnosis of s-IBM.